Are labour relations and leadership styles significantly associated? An empirical study in ten manufacturing firms in Sri Lanka - Opatha, H.H.D.N.P. (Sekolah Pengurusan, Universiti Utara Malaysia, 2003)
It was theoretically argued that Labour Relations (LR) and leadership styles of managers were associated. An empirical study was conducted to test whether the variable of leadership style of managers was significantly associated with the variable of LR in manufacturing firms in Sri Lanka. The study was conducted in ten Sri Lanka manufacturing firms, which were listed unionised companies. The unit of analysis of this study were manager. The results indicated that leadership styles of managers and LR were not significantly associated suggesting that LR is independent of leadership styles of managers in the manufacturing firms studied in Sri Lanka.